2014
DOI: 10.3389/fpsyg.2014.00245
|View full text |Cite
|
Sign up to set email alerts
|

Brain reorganization as a function of walking experience in 12-month-old infants: implications for the development of manual laterality

Abstract: Hand preference in infancy is marked by many developmental shifts in hand use and arm coupling as infants reach for and manipulate objects. Research has linked these early shifts in hand use to the emergence of fundamental postural–locomotor milestones. Specifically, it was found that bimanual reaching declines when infants learn to sit; increases if infants begin to scoot in a sitting posture; declines when infants begin to crawl on hands and knees; and increases again when infants start walking upright. Why … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…In primates, bipedality has also been shown to be associated with enhanced manual lateralization (e.g., [8,10,37,38]). Bipedalism, along with other factors [3,24], has been suggested as a catalyst for the emergence of robust handedness in humans [8,39]. Our findings on marsupials further emphasize the role of bipedality in the evolution of manual lateralization.…”
supporting
confidence: 60%
“…In primates, bipedality has also been shown to be associated with enhanced manual lateralization (e.g., [8,10,37,38]). Bipedalism, along with other factors [3,24], has been suggested as a catalyst for the emergence of robust handedness in humans [8,39]. Our findings on marsupials further emphasize the role of bipedality in the evolution of manual lateralization.…”
supporting
confidence: 60%
“…With more than 5500 article views and an AM score of more than 50 by the time this editorial was written, this article has gained more online attention than almost any other work published in Frontiers in Cognition. Other authors investigated visual lateralization (Asanowicz et al, 2013 ; Pellicano et al, 2013 ; Helon and Króliczak, 2014 ), asymmetries in emotional processing (Propper and Brunyé, 2013 ; Grimshaw and Carmel, 2014 ), behavioral lateralization (Morton, 2013 ; Corbetta et al, 2014 ), and asymmetries in face (Coronel and Federmeier, 2014 ) and body representation (Hach and Schütz-Bosbach, 2014 ), as well as in word generation (Meyer et al, 2014 ) and word recognition (Izura et al, 2014 ). Finally, some authors also investigated the impact of lateralized processing on executive functioning, the topic which had initially inspired this Research Topic (Marsh et al, 2013 ; Ocklenburg et al, 2013a ; Kéïta et al, 2014 ; Stock and Beste, 2014 ).…”
mentioning
confidence: 99%
“…Such differentiation is highly task‐dependent, however, and many actions in which the hands act in complementary roles emerge early in the second year (Bruner, ; Kimmerle et al, ; Kimmerle et al, ; Potier et al, ; Ramsay & Weber, ) or even later (Brakke et al, ; Connolly & Dalgleish, ; Fagard & Jacquet, ). Kimmerle et al () have suggested that this shift in infants’ approach to manipulation represents a transition in neural control of the hands, perhaps related to the fluctuations in coordination tendencies that Corbetta et al () observed and related to the onset of walking.…”
Section: Establishing Toddlers’ Readiness For Phase Explorationmentioning
confidence: 99%
“…Corbetta and Thelen () have examined the coordinative tendencies of infant reaching throughout the first year of life and found that the tendencies to use one or both hands fluctuate throughout the year, starting with the earliest reaching actions (see also Fagard & Pezé, ; Goldfield & Michel, ; Ramsay, ). The research on infant bimanual action has also suggested that the fluctuating use of one or two hands during the first year appears to be linked to fluctuations in the strength of neural coupling (Corbetta, Friedman, & Bell, ; Fagard & Pezé, ), often accompanying the emergence of new behaviors in other domains such as reduplicated babbling (Ramsay, ) or walking (Corbetta & Bojczyk, ).…”
Section: Establishing Toddlers’ Readiness For Phase Explorationmentioning
confidence: 99%